Reproductive health problem among youths and associated factors in Dilla town, southern Ethiopia - Sertsewold, Seblewongel Gebretsadik; Zenebe, Getachew Assefa; Gebrekidan, Amanuel Yosef (Frontiers in Reproductive Health, 2025)
IntroductionAdolescents are defined by the World Health Organization as people aged 10–19, youth 15–24, and young people 10–24. Youth are a demographic that experiences life-threatening physical, emotional, mental, and social changes. Most young individuals are therefore more vulnerable to reproductive health problems than adults for a number of reasons.MethodsA community-based cross-sectional study was done in Dilla town between January and March 2024 with 536 youths. A survey of houses with young people was followed by the use of a systematic sampling technique. Data was gathered using pretested and structured questionnaires. Coded and entered into EPI INFO version 7 after being verified for completeness, it was then exported to SPSS version 22 for analysis. Both multivariate and bivariate logistic regression were performed. Variables with a p-value <0.2 in bi-variable logistic regression were moved to multivariable logistic regression, and variables with a p-value of <0.05 in multivariable logistic regression were considered statistically significant.ResultA total of 493 youths participated in this study, with a response rate of 92%. Among them, 271 (55%) of them were under the age group of 21–25 years old, 225 (45.6%) were females, and 214 (43.4%) were protestants. In addition, 287 (58.2%) said that they are ashamed to discuss sexual issues, and a few respondents, 158 (32%), had multiple sexual partners. Most of the respondents (92.1%, 87.4%, 100%, and 72.6%) reported that they had no history of khat chewing, cigarette smoking, shisha smoking, or drinking alcohol, respectively. The overall youth reproductive health problem in Dilla town is 66.1% (95% CI: 62.5–70.4). Being in the age category 21–25 (AOR: 8.52; 95% CI: 4.61–15.76), employed (AOR: 2.12; 95% CI: 1.09–4.13), ashamed to discuss sexual issues (AOR: 6.66; 95% CI: 3.79–11.71), having multiple sexual partners (AOR: 2.01; 95% CI: 1.08–3.73), not using condoms (AOR: 4.05; 95% CI: 2.31–7.11), health facility inconvenience (AOR: 3.2; 95% CI: 1.85–5.55), and drinking alcohol (AOR: 2.28; 95% CI: 1.29–3.99) were found to be significantly associated with youth reproductive health problems.Conclusion and recommendationHealthcare facilities should provide comprehensive, age-appropriate, and accurate sexual education as part of specialized reproductive health services for youth that prioritize privacy and nonjudgmental treatment. In addition, screening and early detection of RH problems and engaging in community outreach programs are some of the recommended activities.